Reading Proclus and the Book of Causes, Volume 3 On Causes and the Noetic Triad - Calma, Dragos (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2022)
This volume gathers contributions on key concepts elaborated in the Platonic tradition (Proclus, Plotinus, Porphyry or Sallustius) and reconsidered by Arabic (e.g. Avicenna, the Book of Causes), Byzantine (e.g. Maximus the Confessor, Ioane Petritsi) and Latin authors (e.g. Albert the Great, Thomas Aquinas etc.).; Readership: Scholars, students and large audience interested in Greek Neoplatonism and the Long Middle Ages broadly considered (comprising Arabic, Byzantine, Latin, Georgian), with particular focus on causality and the noetic triad being-life-intellect.